Primary treatment of dairy wastewater using bio based natural coagualnts. (2022) - Deepa, D.; Keerthana, R.; Pratheep Kumar, R.; Suryaprakash, R.
Abstract: The dairy industry is one of the major sources of food processing industries which produce a huge amount of wastewater that may adversely affect the environment if discharged untreated. Dairy effluents degrade quickly, depleting dissolved oxygen levels in receiving streams and causing anaerobic conditions. Color, pH, turbidity, total solids, total suspended solids, sulphate, chloride, BOD, COD, and other characteristics are commonly used to characterise such effluent. Coagulation is an important aspect of the wastewater treatment process since it removes the majority of the chemicals that make the water unclean. Chemical coagulants such as alum, ferric chloride, ferric sulphate, and others have been employed in the past. Recent research suggests that these compounds, which are present in small amounts even in treated water, have an influence on the environment when the treated water is reused. As a result, we chose natural plant-based coagulants for the treatment of dairy wastewater in this study and assessed their efficacy. Natural coagulants such as Cicer Arietinum, Moringa Oleifera, and Strychnos Potatorum were used in our research.